Treatment strategies for patients with decompensated liver cirrhosis due to hepatitis C virus infection eligible for liver transplantation: real-life data from five German transplant centers. Issue 8 (August 2019) - Sandmann, Lisa; Dörge, Petra; Wranke, Anika; Vermehren, Johannes; Welzel, Tania M.; Berg, Christoph P.; Grottenthaler, Julia M.; Weiss, Karl-Heinz; Langel, Jessica; Sterneck, Martina; von Wulffen, Moritz; Manns, Michael P.; et al.
Abstract : Background: Even with highly effective direct-acting antivirals (DAAs) treatment of patients with decompensated hepatitis C (HCV) cirrhosis remains challenging. Clinical deterioration and the need for liver transplantation (LT) may arise despite previous antiviral treatment. It is unclear whether in patients with high Model for End-Stage Liver Disease (MELD) antiviral treatment is too risky and should thus be deferred until after LT. Treatment choices that are currently made in the real-world setting are unclear. Methods: We performed a retrospective multicenter data analysis of patients with decompensated HCV cirrhosis (MELD ≥15) that presented to liver transplant centers that are part of the German Center for Infection Research when highly active DAA therapy was available. Choice of treatment strategy (DAA first vs. transplantation first) was analyzed and correlated with baseline and outcome parameters. Results: Thirty-five patients fulfilled the inclusion criteria and their mean MELD score was 18.5±3.78 (median: 17, interquartile range=16–19). In the majority of patients (85.7%) DAA therapy was initiated before LT; survival rates and change in MELD were numerically better in this group compared with those where DAA therapy was withheld (82.1 vs. 40%, P =0.078; ΔMELD: −2.68±6.2 vs. 5.8±14.4, P =0.157). However, DAA treatment was more often initiated in patients with better liver function (MELD: 18±3.54 vs. 21.8±3.9, P =0.008). Three patients discontinued DAA treatment because of clinical deterioration; these patients all had a MELD score above 20 at the start of therapy. Conclusion: At liver transplant centers in Germany DAA before LT is attempted in the majority of cases. It appears to be associated with an improved outcome and seems safe at least in individuals with MELD below or equal to 20. Abstract : Supplemental Digital Content is available in the text.